34.8k views
0 votes
This is Adele’s solution for the equation.

x² - 8x – 33 = 0
Step 1: x² - 8x = 33
Step 2: x² - 8x + 16 = 33 + 16
Step 3: (x – 4)² = 49
Step 4: x – 4 = 49 OR x – 4 = - 49
Step 5: x = 53 OR x = - 45
Where did Adele make her mistake? What are the solutions to this equation? Show all of your work.

User Khusrav
by
6.2k points

2 Answers

5 votes

Answer:

B

Explanation:

I'm pretty sure

User Atulkhatri
by
5.7k points
1 vote

The mistake was in step 1. Here is how to correctly solve the equation:

x² - 8x – 33 = 0

(x - 11) (x + 3) = 0

x – 11 = 0

x +3 = 0

x = 11 and x = -3

User MrKodx
by
6.5k points